LANGKAH-LANGKAH PENENTUAN SUATU BARISAN - L., Erly (MATEMATIKA, 2008)
Consider a non increasing sequence of non negative integres d = (d1, d2, …, dn) . A sequence d is called a graphic if it is sequnce of degrees on a simple graph with n order. In this paper will be discussed necessary and sufficient conditions of a sequence d be a graphic. And then will be constructed an algorithm to determine a sequence be a graphic, particularly a sequnce with n large order.